MAPPING AND ANALYSIS OF LAND SUBSIDENCE RISK MANAGEMENT IN CITIES AROUND THE WORLD - Nurhadianto, Adam
As the world's population continues to grow, groundwater use and infrastructure development are increasing rapidly. This can lead to land subsidence. As a result, risks or negative impacts will arise from this phenomenon. These risks can be prevented by risk management measures. The purpose of this study is to map the rate of land subsidence in cities around the world and analyze the risk management that has been carried out in the city to reduce the phenomenon of land subsidence. The methodologies used are literature study, data collection on land subsidence rate and risk management, mapping, and descriptive analysis. The input parameters used in this study are land subsidence rate data and risk management data from 98 cities in 28 countries that have been collected. Mapping was done to show the distribution of cities experiencing land subsidence, the type of cause, and the rate of land subsidence in the city. Graphing was also done to show the pattern of subsidence accumulation using interpolation and extrapolation methods. Then, the results of the graph were analyzed by linking the risk management that has been carried out in these cities. Based on the graph results obtained, several cities have land subsidence patterns that have sloped, indicating that they have successfully implemented risk management so that land subsidence can be reduced. The analysis shows that risk management in the form of groundwater pumping management with government regulations or groundwater recharge can effectively reduce land subsidence. This is evidenced by the reduced subsidence pattern after this risk management is implemented.